DESIGN FOR SIX SIGMA - Liem Ferryanto (Institute of Research and Community Outreach - Petra Christian University, 2007)
This article provides a step by step process of executing analytical or computer based Design for Six Sigma using a Sliding Door project as an example. It comprises of identification of Voice Of the Customer (VOC), transformation of VOC to what it is called Critical To Quality characteristics (CTQs), modeling of system transfers function, optimal and robust solutions, and tolerance design approach